Exploration of standardized inquiry training software “Yask” - TAN You-hai, JIN Zhao-heng, ZHANG Rui, WANG Jing, SHEN Peng-cheng (Jichu yixue yu linchuang, 2020)
Inquiry is an essential component of diagnostics and one of the essential skills that a clinician required. In order to improve the efficiency of learning inquiry, communication skills, clinical consultation skills, it is worth developing a training model that stimulates inquiry with standardized computer virtualization software. Through the investigation in the early stage with medical students, our team has developed an inquiry simulation software “Yask” with choosing form and made some explorations of reasonable evaluation of inquiry results.